(untitled) (Al-Aasar, 2025)
This research article explores the portrayal of human issues in the poetry of Ayaz Mahmood Ayaz, a distinguished modern Urdu poet, journalist, and columnist. His poetic expression reflects the social, moral, and emotional challenges of contemporary human life with remarkable depth and sensitivity. Ayaz addresses subjects such as poverty, injustice, corruption, loneliness, and the moral decay of society. His poetry also highlights compassion for the oppressed, concern for women’s rights, and the struggles of expatriates. Combining romanticism with realism, Ayaz presents a vivid and truthful picture of human life and its complexities. His simple yet powerful language makes his poetry both accessible and profound. Through his works, he not only portrays human suffering and social imbalance but also emphasizes truth, justice, and ethical awareness. Ayaz’s poetry stands as a genuine reflection of humanity, embodying sincerity, empathy, and philosophical insight.